Predictors of Developmental Patterns of Obesity in Young Children - Thomas G. O'Connor; Thomas G. O'Connor; Thomas G. O'Connor; Thomas G. O'Connor; Thomas G. O'Connor; Jason Williams; Clancy Blair; Lisa M. Gatzke-Kopp; Lori Francis; Michael T. Willoughby (Frontiers Media S.A., 2020)
Introduction: The current study characterizes longitudinal patterns in obesity in young children and their prediction from developmental programming and social determinant hypotheses.Materials and Methods: The data are based on the Family Life Project, a prospective longitudinal study of 1,292 families recruited from low-income, racially diverse, rural communities in Pennsylvania, and North Carolina. Pre-natal, peri-natal, and post-natal risks for childhood obesity were collected from 2 months of age; in-person assessments of child growth were used to identity obesity on multiple occasions from 24 to 90 months of age.Results: Two major novel findings emerged. First, longitudinal analyses identified four distinct obesity development profiles: stable obesity, later-onset obesity, moderate/declining obesity, and non-obese; these groups had distinct risk profiles. Second, prediction analyses favored developmental programming explanations for obesity, including evidence even in early childhood that both low- and high birth weight was associated with stable obesity. There was no indication that pre- and peri-natal and post-natal factors predicted obesity differently in non-minority and minority children.Discussion: Factors derived from the developmental programming model of obesity overlapped with, but predicted early onset obesity independently from, risks associated with social determinant models of obesity.